An Improved Atmospheric Phase Compensation Approach to Ground-based SAR Interferometry for Landslide Monitoring. (February 2019) - Zha, Zhenzhu; Yang, Yue; Chen, Xinyu; Long, Keyu; Wan, Qun
Abstract: Ground-based synthetic aperture radar (GB-SAR) interferometry is an increasingly popular terrestrial remote sensing technique for landslide monitoring. However, in actual application, the atmospheric phase screen (APS) seriously affects the accuracy of GB-SAR interferometry. Therefore, it is necessary to estimate the APS accurately. This paper develops an improved APS compensation method based on a 2D-polynomial regression model (2D-PRM) with a two-step estimation process using GB-SAR measurements. In this paper, permanent scatterer (PS) points which are selected by a joint method using amplitude, amplitude deviation and correlation coefficient are used to roughly estimate the model parameters. Then, by imposing the condition of the standard deviation of the fitting error, the outliers whose values enormously affect the estimation of parameters are filtered out of the estimation process. A more efficient estimation of the APS is finally achieved by using the remaining pixels based on 2D-PRM. At last, a landslide monitoring experiment is carried out to verify the performance of the proposed method.